2012
DOI: 10.1007/s10140-012-1038-z
|View full text |Cite
|
Sign up to set email alerts
|

Urgent MRI with MR cholangiopancreatography (MRCP) of acute cholecystitis and related complications: diagnostic role and spectrum of imaging findings

Abstract: Acute cholecystitis, which is usually associated with gallstones, is one of the commonest surgical causes of emergency hospital admission and may be further complicated by mural necrosis, perforation, and abscess formation. Magnetic resonance imaging (MRI) is increasingly available in the emergency setting. Technically improved equipment and faster acquisition protocols allow excellent tissue contrast and MRI is now an attractive modality for imaging acute abdominal disorders. The use of MRI with MR cholangiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…Age, yearsDiscussion MRI imaging typically reveals gallbladder wall thickening and pericholecystic fluid in patients with acute cholecystitis (23), and is reported to be superior to CT for the diagnosis of acute cholecystitis (24). In the present study, DWIBS/T2 was as successful as CT imaging in identifying wall thickening and pericholecystic inflammation.…”
Section: Liver Inflammationsupporting
confidence: 52%
“…Age, yearsDiscussion MRI imaging typically reveals gallbladder wall thickening and pericholecystic fluid in patients with acute cholecystitis (23), and is reported to be superior to CT for the diagnosis of acute cholecystitis (24). In the present study, DWIBS/T2 was as successful as CT imaging in identifying wall thickening and pericholecystic inflammation.…”
Section: Liver Inflammationsupporting
confidence: 52%
“…Therefore, measurements of wall thickness may be useful in aiding the diagnosis of acute cholecystitis and in evaluating its severity (22). In particular, the detection of wall thickening and pericholecystic fluid by MRI may be a useful diagnostic tool (23). In the present study, the gallbladder wall of patients with acute cholecystitis was thickened.…”
Section: Discussionmentioning
confidence: 51%
“…Recent studies have even suggested the systematic use of MRCP in patients with acute cholecystitis to exclude CBDS [1,15,16] . Another option is EUS, an invasive test with a sensitivity of 93% and a specificity of 96% for detection of choledocholithiasis [14] but with a lower morbidity than ERCP.…”
Section: Discussionmentioning
confidence: 99%